PENGARUH HUKUM ALAM DALAM PEMBENTUKAN PENGADILAN PIDANA INTERNASIONAL TERHADAP KEJAHATAN SERIUS ATAS HAK ASASI MANUSIA - Danel Aditia Situngkir (Ensiklopedia Sosial Review, 2022)
Natural law in principle rests on social justice in law. The concept of social justice is the principle that courts (judges) cannot reject cases. Natural law is not a finished legal system. Natural law provides a direction of view in the formation of regulations. After World War II, which caused enormous casualties, both countries and international organizations worked together to pay attention to human rights. The influence of Natural Law in the establishment of an ad hoc international tribunal to try crimes against peace, war crimes, crimes against humanity, laws or customs of war, genocide which is included in the classification of international crimes which are ius cogens because the doctrine of natural law focuses on human consciousness and rational thinking. (human reason) that these crimes are evil and what has been done can be accepted as a crime by anyone, anywhere and anytime. The teachings of Natural Law are in opposition to teachings with immunity for someone who carries out orders based on domestic law that applies in his country. The establishment of the International Criminal Court is an answer to the natural law view of past events where to try the perpetrators of serious crimes against human rights an ad hoc international criminal court was formed which violated the provisions that had been considered rigid as law by positivists. The view of natural law finally gives the view that international crimes are part of the jus cogens codified into positive law in the Rome Statute. The method used is a normative juridical approach by looking at the history of the establishment of an ad-hoc international criminal court and the International Criminal Court which is then used as a reference to analyze how the influence of natural law teachings in the formation of these courts is in the context of law enforcement for crimes against human rights. The researcher will base his research on the teachings of natural law, the principles of international law that underlie the formation of international statutes or agreements in the establishment of the Adhoc International Criminal Court and the International Criminal Court.Keywords: Natural Law, International Criminal Court, Human Rights